Avian predators as a biological control system of common vole (Microtus arvalis) populations in NW Spain: experimental set-up and preliminary results - Jareño, D. (Julius-Kühn-Archiv, 2011)
Ecologically-based pest management using biological control has been successfully tested elsewhere, but it has never been evaluated for cyclic vole plagues in Europe. We report the first large-scale replicated experiment to study the usefulness of artificially increasing populations of Common kestrels (Falco tinnunculus) and Barn owls (Tyto alba) to control common vole populations in agricultural habitats where nesting sites for raptors are scarce. The first preliminary results suggest: 1) population density of both predator species may be increasing in response to both nest-site availability and rodent density; 2) voles are a major prey; and 3) vole density during an increase phase of the population cycle may be reduced near nest-boxes.